Zastosowanie swapów towarowych w zarządzaniu ryzykiem cenowym na rynkach towarowych - Tomaszewski, Jacek (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
Dramatic increase in the use of derivatives instruments as the tools commodity price risk management has been observed over the course of recent years. New types of instruments are designed that can better match risk profiles of the commodity market participants. One of the newly introduced instruments is commodity swap, offered for the first time in the mid 1980’s. Particularly large increase in the volume and value of these transactions has been recorded during the first decade of the XXI-st century. The basic commodity swap is a transaction between two parties which calls for the single or multiple exchange of cash flows where the value of these cash flows is dependent on the price of commodity (or basket of commodities) underlying the contract. Entering into commodity swap as a risk management tool allows fixing the price of the underlying commodity over long term time horizon. Commodity swap are used most extensively as a risk management instrument for energy commodities and for commodities with no active commodity futures markets that are considered prime alternative to swaps. In the last few years energy companies listed on the Warsaw Stock Exchange began to use commodity swaps, primarily for the purpose of fixing purchase price of oil and gas – major cost components for these companies.